Research on technology use in multicultural settings - Ganesh, Tirupalavanam G.; Boriack, Anna W.; Stillisano, Jacqueline R.; Davis, Trina J.; Waxman, Hersh C. (Research in educational diversity and excellence., 2015)
This book is the third volume in the series on Research in Educational Diversity and Excellence. The goal of this series is to bring issues of diversity and educational risk to the forefront of national attention in order to assist the nation's diverse students at risk of failure to achieve academic excellence. This series focuses on critical issues in the education of linguistic and cultural minority students and those placed at risk by factors of race, poverty, and geographic location.The purpose of the present book is to summarize and discuss recent perspectives, research, and practices related to the use of educational technology in multicultural settings. Technology that is already ubiquitous in our daily lives brings a myriad of issues to the area of education. Although educational systems should be geared to address challenges appropriately, the systems should be designed and developed to provide opportunities to take advantage of technology use. This book is noteworthy in that it presents a variety of theoretical and practical considerations for technology use in diverse multicultural contexts. Consisting of 12 chapters, the book (a) proposes theoretical concerns for understanding technological learning environments today and envisions the potential impact of future technology use and (b) examines technology tools and models that have been used for interventions, programs, and projects and measures and documents specific outcomes and challenges involving complex interactions within low-income and languageminority families and students.